(untitled) (Research, Society and Development, 2022)
This research investigates the alignment between the strategies practiced and the organizational mission of a nonprofit institution. A reflection on the challenges faced in the management field, forcing it to rethink its mission and its way of acting. These organizations have adapted some values and converted previously informal processes into modern managerial practices of business logic. The case study, carried out under the qualitative perspective, whose main methodological support of data analysis was based on content analysis, with the objective of identifying if the strategies practiced in the organization are aligned with its social mission. The research results showed that the social management strategy perspective gains complexity in the construction process, with greater use of emerging strategies, which is justified by the abrupt changes that occur in the day-to-day of the organization.